Computing Parameter Estimates of a Homogeneous Nested Piecewise Linear Regression - Noskov, S. I.; Belinskaya, S. I. (Vestnik Dagestanskogo gosudarstvennogo tehničeskogo universiteta. Tehničeskie nauki (Online), 2024)
Objective . The aim of the study is to develop an algorithm for identifying the parameters of a homogeneous nested piecewise linear regression model of the first type by the method of least modules. Method . Estimation of its unknown parameters is carried out with the help of reduction to the problem of linear Boolean programming. Its solution should not cause computational difficulties due to a significant number of effective software tools - for example, the well-established and freely available program LPsolve on the Internet. Result . The generated linear programming problem has an acceptable dimension for solving practical modeling problems. Conclusion . The results of solving a numerical example indicate the effectiveness of the method proposed in the work for calculating parameter estimates for a homogeneous nested piecewise linear regression model of the first type by the method of least modules.